Development of Problem-based Motion Graphic Video on the Global Warming Theme to practice High-Level Thinking Skills and Collaborative Ability for Junior High School Students - Rani, Widiyastuti Jaya; Wusqo, Indah Urwatin (Universitas Negeri Semarang, 2021)
Higher order thinking skills are an important part of the 21st century because it demands that a teacher be able to foster students' thinking abilities. In addition, the demands for special skills that need to be empowered in learning activities that must be possessed are collaboration skills. The results of the observations show that SMP N 38 Semarang still needs to be developed to deliver students to have higher-order thinking skills and collaboration abilities. Problem-based motion graphic video media is one of the media developed to train higher-order thinking skills and collaboration skills of students. The results of the feasibility analysis of the media before being tested were very feasible with an average percentage of 95.8% of the results of the media experts and 92.6% of the results of the validation of the material experts. The characteristics of video motion graphics are (1) a two-dimensional animation media, (2) the motion graphics developed based on the characteristics of problem-based learning, (3) contain question exercises combined with motion graphics that can train students' high-order thinking skills, (4) there are discussion activities that can train collaboration skills, (5) it can be used anytime and anywhere. The results of the analysis of high-order thinking skills of students got a percentage of 68% in the good category. The results of the discussion analysis on collaboration ability get a percentage of above 62.5% in the very good category and the good category.